Anomalous azimuthal variations with 360° periodicity of Rayleigh phase velocities observed in Scandinavia. Issue 3 (13th November 2020) - Mauerberger, Alexandra; Maupin, Valérie; Gudmundsson, Ólafur; Tilmann, Frederik
SUMMARY: We use the recently deployed ScanArray network of broad-band stations covering most of Norway and Sweden as well as parts of Finland to analyse the propagation of Rayleigh waves in Scandinavia. Applying an array beamforming technique to teleseismic records from ScanArray and permanent stations in the study region, in total 159 stations with a typical station distance of about 70 km, we obtain phase velocities for three subregions, which collectively cover most of Scandinavia (excluding southern Norway). The average phase dispersion curves are similar for all three subregions. They resemble the dispersion previously observed for the South Baltic craton and are about 1 per cent slower than the North Baltic shield phase velocities for periods between 40 and 80 s. However, a remarkable sin(1 θ ) phase velocity variation with azimuth is observed for periods >35 s with a 5 per cent deviation between the maximum and minimum velocities, more than the overall lateral variation in average velocity. Such a variation, which is incompatible with seismic anisotropy, occurs in northern Scandinavia and southern Norway/Sweden but not in the central study area. The maximum and minimum velocities were measured for backazimuths of 120° and 300°, respectively. These directions are perpendicular to a step in the lithosphere–asthenosphere boundary (LAB) inferred by previous studies in southern Norway/Sweden, suggesting a relation to large lithospheric heterogeneity. In order to test this hypothesis, we carried out 2-D full-waveform modeling of Rayleigh wave propagation in synthetic models which incorporate a steep gradient in the LAB in combination with a pronounced reduction in the shear velocity below the LAB. This setup reproduces the observations qualitatively, and results in higher phase velocities for propagation in the direction of shallowing LAB, and lower ones for propagation in the direction of deepening LAB, probably due to the interference of forward scattered and reflected surface wave energy with the fundamental mode. Therefore, the reduction in lithospheric thickness towards southern Norway in the south, and towards the Atlantic ocean in the north provide a plausible explanation for the observed azimuthal variations.